Nordic Brands Through Chinese Eyes: A Study on the Country Image, Brand Benefits, and Consumer Ethnocentrism - Tan,Chujun; Shen,Qianhua (2025)
This study focuses on the perception of Nordic brands by Chinese consumers in the context of cross-cultural brand communication, with an emphasis on the influence of the country-of-origin (COO) effect and consumer ethnocentrism on brand attitude and purchase intention. The research adopts quantitative methods, through online questionnaire surveys. Consumers’ responses from new first-tier, first-tier and second-tier cities in China, who are familiar with Nordic brands and not engaged in related industries, are collected. The research shows that both country image and brand benefits significantly affect brand attitude, which mediates their impact on purchase intention. Among them, the emotional and symbolic dimensions are particularly influential. Consumer ethnocentrism has not significantly moderated the relationship between country image and brand attitude, but it moderates the effect of symbolic brand benefits and directly weakens brand attitude. This study deepens the understanding of how the country-of-origin effect and consumer psychological variables interact in the Chinese consuming market to influence brand attitudes, and also provides empirical support for Nordic brands to formulate more culturally sensitive and affectively resonant brand communication strategies in China.
Keywords: Country-of-Origin Effect; Country Image; Consumer Ethnocentrism; Brand Attitude; Brand Benefits; Purchase Intention; Cross-Cultural Brand Communication; Chinese Consumers; Nordic Countries; Nordic Brands